A tribute to an outstanding pioneer acarologist of Iran, Prof. Dr. Hossein Sepasgosarian - Alireza Saboori (Persian Journal of Acarology)
A tribute to an outstanding pioneer acarologist of Iran, Prof. Dr. Hossein Sepasgosarian.